2017
DOI: 10.5546/aap.2017.eng.212
|View full text |Cite
|
Sign up to set email alerts
|

Emotional exhaustion is associated with work related stressors: a cross-sectional multicenter study in Malaysian public hospitals

Abstract: Introduction.Emotional exhaustion is an important component of burnout. Burnout is common among doctors. It affects the physical and mental health of doctors, their performance and the quality of care they provide. This study aimed to investigate the level and factors associated with emotional exhaustion among doctors in pediatric practice in Malaysia. Population and methods. A self-administered questionnaire was used in this multicenter cross-sectional study. It included questions on the socio-demographics, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
(53 reference statements)
5
12
0
1
Order By: Relevance
“…In addition, multiple work-related stressors were significantly associated with burnout among family medicine residents in this study. Consistent with previous burnout literature across different specialties,[510112930] residents who perceived various stressors like work overload or having to do work outside one's competencies and those who perceived work nature as mentally straining showed positive relationships with burnout in this study. Literature highlighted that burnout catalyzes serious personal repercussions like substance abuse,[31] family conflicts,[32] and suicidal ideation,[33] and much catastrophically compromising the efficacy of health care delivery system through increased medical errors.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In addition, multiple work-related stressors were significantly associated with burnout among family medicine residents in this study. Consistent with previous burnout literature across different specialties,[510112930] residents who perceived various stressors like work overload or having to do work outside one's competencies and those who perceived work nature as mentally straining showed positive relationships with burnout in this study. Literature highlighted that burnout catalyzes serious personal repercussions like substance abuse,[31] family conflicts,[32] and suicidal ideation,[33] and much catastrophically compromising the efficacy of health care delivery system through increased medical errors.…”
Section: Discussionsupporting
confidence: 88%
“…[35] As residents undergo deeper insights of continuous medical education and training, previous studies have highlighted significant associations between other organization-related stressors with burnout. [11] This study found that performance pressures that impose time limitations were significantly associated with family medicine residents’ burnout. Concurrently, organizational attributes that demand unrealistic goals and having incompetent or disrespectful interactions with colleagues were significantly associated with burnout.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations